Prevalence of Malnutrition Among Children Under Five in Iware, Taraba State - Isaac John Umaru; Solomon O. Asare; Tyem Lawal Danjuma; Atsu Ayi; Ingwu Joseph Akem; Usenobong Morgan Akpan; Julius Ishaya Salman; George Okra Hassan; Maryam Usman Ahmed; Hauwa A. Umaru (Darul Yasin Al Sys, 2026)
Malnutrition remains a major public health challenge in Nigeria, particularly among children under five years of age, with serious consequences for morbidity, mortality, cognitive development, and long-term human capital. In rural communities such as Iware, Taraba State, this burden is intensified by poverty, poor feeding practices, limited access to healthcare, and low caregiver education. This study aimed to determine the prevalence of stunting, wasting, and underweight among children aged 0–59 months in Iware and to examine the associations between nutritional status and socio-economic factors, including household income, caregiver education, feeding practices, and recent illness episodes, while also assessing the coverage of exclusive breastfeeding and vitamin A supplementation. A cross-sectional design was employed, with a sample size estimated using Cochran’s formula at 200–400 children. A multistage sampling technique was used in which households were randomly selected and eligible children were stratified by age group. Data were collected through a structured questionnaire on socio-demographic characteristics, feeding practices, and household conditions, alongside anthropometric measurements of weight, height/length, and mid-upper arm circumference, with nutritional status classified according to WHO Growth Standards. Data collection was conducted over 2–4 weeks by trained enumerators following a pilot study, and the data were analyzed using SPSS and STATA through descriptive statistics, chi-square tests, and logistic regression. The findings revealed a high prevalence of malnutrition, with stunting at 35%, underweight at 30%, and wasting at 25%. Although 60% of children were exclusively breastfed and 65% had received vitamin A supplementation, 42.5% had experienced recent illness. Socio-economic findings further showed that 72.5% of households earned below ₦30,000 per month and that 20% of caregivers had no formal education. Statistical analysis indicated significant associations between malnutrition and low household income, poor caregiver education, and inadequate complementary feeding practices (p < 0.05). The study concludes that malnutrition among children under five in Iware is driven by the combined effects of chronic poverty, limited maternal education, suboptimal feeding practices, and frequent illness. These findings underscore the need for multi-sectoral interventions focused on nutrition education, economic empowerment, improved healthcare access, and community-based strategies tailored to rural populations.